Analisis Butir Soal Materi Rantai Makanan Meliputi Validitas, Reliabilitas, Tingkat Kesukaran, dan Daya Beda (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This research is motivated by the importance of the availability of quality evaluation instruments to accurately measure student learning outcomes, especially in the Natural and Social Sciences (IPAS) subject matter. The quality of a test instrument greatly determines the validity of the learning outcome data obtained, but in practice, it is still often found that test items have not gone through the qualitative and quantitative parameter analysis stages. This study aims to analyze and describe the quality of the IPS test items on the food chain material in grade V of elementary school in terms of validity, reliability, level of difficulty, and discrimination. The research method used is descriptive quantitative with 19 fifth grade students of Growong Kidul 02 Elementary School as test subjects. Data were collected through an objective test instrument in the form of 25 multiple choice questions which were then processed using the Microsoft Excel program. The research findings show that of the total 25 test items tested, 18 items were declared valid and had an adequate level of reliability to be used as a measuring tool. The results of the difficulty level analysis show a varied distribution of questions, including easy, medium, and difficult categories. Meanwhile, in terms of discriminatory power, a diversity of question quality was found, ranging from poor, adequate, good, to excellent. The implication of this study is the availability of a standardized assessment instrument for the food chain topic that can serve as a reference for teachers at Elementary School in conducting learning evaluations. However, the results of this study also provide recommendations for improvements or revisions to items with low discriminatory power to optimize the overall quality of the instrument for future use.